RANCANG BANGUN SISTEM INFORMASI KURIKULUM 2013 TINGKAT SEKOLAH DASAR BERBASIS WEB DENGAN SDLC WATERFALL - Yulianto, Susilo Veri; Atmaja, Ardian Prima (Department of Information Systems, Institut Teknologi Sepuluh Nopember, 2018)
In 2014, Indonesian Government implemented Curriculum 2013 which replaces KTSP (Kurikulum Tingkat Satuan Pendidikan). In the assessments of Curriculum 2013, some schools already used Microsoft Excel program. Hovewer this program has a disadvantage, such as less structured data which causing the need of data re-entry in the next semester. For this problem, a software or web-based information system is needed to help make the assessment process easier and faster. Web-based information system needs to be installed on a server computer, then the information system can be accessed by client using a web browser (mozilla, chrome, etc.) trough computer network. The development of this information system using PHP programming language, codeigniter framework, and System Development Life Cycle (SDLC) waterfall model.